Determinación del coeficiente de cultivo kc para tomate lycopersicon esculentum l bajo invernadero en la granja Santa Ines - Llumiluisa Juela, Darío Javier (2017)
Agriculture and food production are the activities that demand the most water worldwide, water an essential natural resource for the development of cultivars is losing both quantitatively and qualitatively. The water requirements are subject to several factors including climate, water demand depending on the type and stage of development of the crop; and therefore, it is necessary to have an efficient control and rational use of water in the irrigation systems; As evapotranspiration (ET) being a natural process of summing the evaporation of the soil surface and transpiration of the plant through the uptake of water in the root; Plays a key role in agricultural research, irrigation planning and water resource management; (ETC), are essential variables for an efficient application and frequency of irrigation according to the needs of the crops. For proper management of irrigation and water saving an accurate estimate is essential for the water needs of the crops, making reference evapotranspiration (ETO) and crop coefficient (KC) one of the key factors for its determination; The understanding of variation and magnitude of the crop coefficient (KC) is important for the accurate determination of crop evapotranspiration (ETC) and to establish correct irrigation slabs for the efficient use of water in agriculture and to ensure the sustainability of The productive systems. The main objective of the experimental work was to determine the KC curve by means of the heavy lysimetric method for the tomato crop (Solanum lycopersicon L.) during its phenological development, under controlled conditions in greenhouse. For the present experimental work we determined the cultivation coefficients taken weekly and separated for vegetative stage, to obtain the KC were used home lysimetric, so that we also determined the water requirements for each vegetative stage using the formulas from the coefficient of culture (KC). For the data collection, 10 tomato plants were randomly collected and the weight was recorded before and after, with a total of 40 experimental units for the determination of ETC, for the ETO the same procedure was used, but with 5 reference crop plants (pasture) taken at random from a total of 10 units. The results obtained from KC for each vegetative stage (initial, development, mid-development and final) were 0.55; 1.05; 1.11 and 0.75 respectively, the greatest water requirements were presented in the development and mid-development stages; and in the final stage it descends since the culture enters a state of physiological maturity. The results obtained from KC for each vegetative stage compared to those exhibited by the FAO present some similarity, so it is recommended to perform the test in different edaphoclimatic conditions, with different varieties and density of sowing.